Is it necessary to sign agreements to avoid double taxation? - Trujillo Gutierrez, Claudia (2024)
Over the years, the Convention to Avoid Double Taxation (hereinafter CDI) has become an important tool for tax law. Foreign investors - when placing their capital - will choose as their first option the country with which they have a CDI signed, and thus avoid double taxation with respect to the activities or investments they carry out. Not all countries have the aforementioned agreements, this being an aspect that foreign investors evaluate to ensure the greatest profitability of their investment. The States and technical teams of each of the countries interested in subscribing to a CDI carry out a series of negotiations in accordance with their legislation. There are some South American countries with great interest in subscribing to CDIs, and in this type of situation the long-term economic advantage generated by their subscription must be evaluated.